2008
DOI: 10.1148/radiol.2493080080
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis: Intravoxel Incoherent Motion MR Imaging—Pilot Study

Abstract: Restricted diffusion observed in patients with cirrhosis may be related to D* variations, which reflect decreased perfusion, as well as alterations in pure molecular water diffusion in cirrhotic livers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
581
11
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(639 citation statements)
references
References 33 publications
40
581
11
7
Order By: Relevance
“…Previously, the use of IVIM imaging was limited to neuroradiologic applications because the abdominal organs can be subject to respiratory and other motion artifacts. The advent of respiratory gating combined with parallel imaging allows IVIM MRI to be attempted in the evaluation of abdominal organs, such as liver (7)(8)(9)(10)(11)(12). Yamada et al (7) were the first to assess IVIM MRI in abdominal organs, although they used only limited number of b values (30, 300, 900, and 1,100 s/mm 2 ), and did not calculate pseudodiffusion values.…”
Section: Introduction and Basic Principles Of Intravoxel Incoherent Mmentioning
confidence: 99%
“…Previously, the use of IVIM imaging was limited to neuroradiologic applications because the abdominal organs can be subject to respiratory and other motion artifacts. The advent of respiratory gating combined with parallel imaging allows IVIM MRI to be attempted in the evaluation of abdominal organs, such as liver (7)(8)(9)(10)(11)(12). Yamada et al (7) were the first to assess IVIM MRI in abdominal organs, although they used only limited number of b values (30, 300, 900, and 1,100 s/mm 2 ), and did not calculate pseudodiffusion values.…”
Section: Introduction and Basic Principles Of Intravoxel Incoherent Mmentioning
confidence: 99%
“…There are reports that D * and ADC values of patients with cirrhosis are significantly lower than in healthy individuals [3]. The increase in portal blood flow due to food intake is larger in healthy people, so it is expected that there will be little effect in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 97%
“…Recent advances in equipment brought the feasibility of IVIM to clinical use. Luciani et al reported that IVIM was useful for diagnosis of liver cirrhosis [3]. They clarified using IVIM that decreasing microcirculation led to the diffusion restriction in liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Second, no pathologic evaluation was performed. Third, the ADC values were calculated by monoexponential analysis of the signal in this study, whereas bi-exponential analysis may have provided more detailed information regarding focal tissue non-invasively [26]. Fourth, recent studies have compared pretreatment of the ADC of the tumor with the tumor reduction ratio.…”
Section: Discussionmentioning
confidence: 99%